Insight into early‐phase trials for lung cancer in the United States. Issue 3 (10th July 2015) - Yang, Jin‐Ji; Wu, Yi‐Long
Abstract: Introduction: Few data have been published comparing early‐phase trials for lung cancer between China and the United States (US). This study was to investigate the differences of phase 1 trials for lung cancer between these two countries. Methods: In 2014, a cross‐sectional survey was conducted to compare phase 1 trials for lung cancer between the Guangdong Lung Cancer Institute (GLCI), the University of Wisconsin Carbone Cancer Center (UWCCC), and the University of Texas MD Anderson Cancer Center (MDACC). Results: We found that the GLCI had a lower percentage of phase 1 lung cancer trials than the MDACC in December 2014 (23.8% [5/21] vs. 59.8% [28/47], P = 0.006) and the UWCCC in September 2014 (16.7% [3/18] vs. 34.8% [8/23], P = 0.345). Descriptive analyses were performed for early‐phase trials conducted by the Cancer Therapy Evaluation Program at the National Cancer Institute (CTEP/NCI), the MDACC, and the Chinese Thoracic Oncology Group (CTONG). There were 149 ongoing early‐phase trials in the Department of Investigational Cancer Therapeutics (Phase 1 program) at the MDACC in October 2014. In contrast, no phase 1 trials had been initiated by the CTONG since its establishment in 2007. Conclusions: These data suggest that a significantly higher percentage of phase 1 trials for lung cancer were conducted in the US than in China. Early‐phase oncology trials with robust preclinical data had a higher chance of being approved by the Investigational Drug Branch at the CTEP/NCI. Given the importance of early‐phase oncology trials in developing innovative cancer medicines, such studies should be highly encouraged and strategically funded in China.